Psychometric Properties of the Sexual Interest and Desire Inventory-Female for Diagnosis of Hypoactive Sexual Desire Disorder: The Persian Version - Malary, Mina (Iran J Psychiatry, 2016)
Objective: Hypoactive sexual desire Disorder (HSDD) is a common sexual problem among women. Sexual interest and desire inventory –female (SIDI-F) has been widely validated and used to measure sexual desire in women. The aim of this study was to determine the psychometric properties of the Persian version of SIDI-F for Iranian population. Method: This was a methodological study on the psychometric properties of SIDI –F. This report describes the process and principles used in the translation and cultural adaptation of the SIDI-F on 40 women of reproductive age who were selected using convenience sampling method. The content validity of this inventory was proved by analyzing the feedback solicited from women of reproductive age; professions specialized in health, sociology and psychology. Reliability was assessed through test-retest and internal consistency reliability. Results: Few cultural differences were identified and considered during the process of translation and validation. In Content Validity Ratio (CVR) measurement, the total score of SIDI-F was higher than Lawsche table (%51 for 14 experts), indicating the importance of including the mentioned items in the tool. CVR scores for all items were equal or more than 0.79. The internal consistency reliability measured for the whole tool was 0.89, showing considerable total reliability. Conclusion: The Persian version of the SIDI-F seems to be valid and reliable and can be used to identify women with low sexual desire through research and sexual health programs provided by the health centers in Iran, and to design appropriate interventions to treat HSDD.